Research on IoV resource allocation algorithm assisted by reconfigurable intelligent surface - Fatang CHEN; Ruofan ZHANG (Tongxin xuebao)
In order to meet the higher requirements of vehicle communication quality and spectral efficiency, a IoV resource allocation algorithm assisted by reconfigurable intelligent surface (RIS) was proposed.The RIS reflection coefficient matrix, power allocation, and spectrum sharing schemes were combined to solve the problem of maximizing the total capacity of V2I link under the condition of ensuring the reliability of V2V link.As this problem was a non-convex optimization problem with highly coupled variables, it was difficult to solve it directly.Therefore, after introducing an analytic expression to approximate the interrupt probability of V2V link, the problem was decomposed into three sub-problems by using the block coordinate descent (BCD) method, and the sub-problems were solved by introducing auxiliary variables, successive convex approximation (SCA), Hungarian algorithm, etc., and then the approximate suboptimal solution of the problem was obtained.Simulation results show that the proposed algorithm has good convergence performance and can effectively improve the total capacity of V2I link.